The Ethics of Survival in Contemporary Literature and Culture
XI, 356 p. 1 illus.
Keywords: The Ethics of Survival provides us with a kaleidoscope of intellectually inquisitive, intriguing and invariably topical perspectives on human suffering, trauma and testimony in close dialogue with the increasingly urgent challenges of both individual and collective care and responsibility. The fourteen original essays expertly assembled here by Freiburg and Bayer reinvigorate and indeed rewrite the global ethics agenda for scholarly debate and critical analysis across the disciplines of literature, philosophy and cultural history, problematizing contemporary quandaries against the background of the Holocaust’s enduringly horrific legacy. The volume launches a thought-provoking intervention into extremely sensitive and controversial terrain where humanity must confront its own fallibility, destructiveness and pain beyond humanism’s much-vaunted catalogue of traditional ideals. —Prof. Berthold Schoene, Faculty Head of Research and Knowledge Exchange for Arts and Humanities, Manchester Metropolitan University, UK The Ethics of Survival in Contemporary Literature and Culture delves into the complex problems involved in all attempts to survive. The essays analyze survival in contemporary prose narratives, short stories, poems, dramas, and theoretical texts, but also in films and other modes of cultural practices. Addressing diverse topics such as memory and forgetting in Holocaust narratives, stories of refugees and asylum seekers, and representations of war, the ethical implications involved in survival in texts and media are brought into a transnational critical discussion. The volume will be of potential interest to a wide range of critics working on ethical issues, the body, and the politics of art and literature Rudolf Freiburg is Professor of English literature at the Friedrich-Alexander-Universität Erlangen-Nürnberg, Germany. He is co-editor and editor of several books, including Swift: The Enigmatic Dean (1998), “But Vindicate the Ways of God to Man”: Literature and Theodicy (2004), Kultbücher (2004), Literatur und Holocaust (2009), Träume (2015), Unendlichkeit (2016), D@tenflut (2017), Sprachwelten (2018) and Täuschungen (2019). He has written many articles on eighteenth-century literature (Joseph Addison, Jonathan Swift, Samuel Johnson), and contemporary literature (John Fowles, Julian Barnes, Ian McEwan, Sebastian Barry). Gerd Bayer is Professor of English literature and culture at the Friedrich-Alexander-Universität Erlangen-Nürnberg, Germany. He has published on contemporary and early modern literature, including Novel Horizons: The Genre Making of Restoration Fiction (2015) and on Holocaust literature and film, most recently as guest editor of a special issue for Holocaust Studies (UK).